Drought stress tolerance in pineapple (Ananas comosus. L. Merrill) varieties / Nur Suraya Abdullah ... [et al.] - Abdullah, Nur Suraya; Abdul Aziz, Noorshilawati; Mohammed, Anisah; Shah Yusop, Mohamad Amir (2011)
Pineapple (Ananas comosus (L) Merrill) was recorded as a crop originated from the arid region of the Central America, and it is believed to be tolerant under drought condition and might be suitable to be cultivated in the BRIS (Beach Ridges Interspersed with Swales) soil area. The BRIS soil contained low water holding capacity, less nutrient and not suitable for cultivation of many crops species. Thus, a study was conducted to examine the effect of mannitol as a drought stress agent on three cultivated varieties (cultivar) of pineapple, namely N36, Morris and Sarawak. with the aim to determine and to select the best pineapple varieties for cultivating under the BRIS soil condition. The results indicated that the growth of pineapple was affected by different concentration of mannitol. The proline content of pineapple was increased with increasing of mannitol concentration however decreased at highest mannitol concentration. Sarawak and Morris varieties were suitable to be selected as the most suitable and profitable pineapple cultivar for cultivating in the BRIS soil area.